Current‐Controlled Topological Magnetic Transformations in a Nanostructured Kagome Magnet. Issue 33 (5th July 2021) - Wei, Wensen; Tang, Jin; Wu, Yaodong; Wang, Yihao; Jiang, Jialiang; Li, Junbo; Soh, Yona; Xiong, Yimin; Tian, Mingliang; Du, Haifeng
Abstract: Topological magnetic charge Q is a fundamental parameter that describes the magnetic domains and determines their intriguing electromagnetic properties. The ability to switch Q in a controlled way by electrical methods allows for flexible manipulation of electromagnetic behavior in future spintronic devices. Here, the room‐temperature current‐controlled topological magnetic transformations between Q  = −1 skyrmions and Q  = 0 stripes or type‐II bubbles in a kagome crystal Fe3 Sn2 are reported. It is shown that reproducible and reversible skyrmion–bubble and skyrmion–stripe transformations can be achieved by tuning the density of nanosecond pulsed current of the order of ≈10 10 A m −2 . Further numerical simulations suggest that spin‐transfer torque combined with Joule thermal heating effects determine the current‐induced topological magnetic transformations. Abstract : Current‐controlled topological skyrmion–bubble and skyrmion–stripe transformations are achieved in a reversible and reproducible way by tuning the nanosecond pulsed current amplitude on the order of ≈10 10 A m −2, which enables future reliable and energy‐efficient manipulation of electromagnetic properties in topological spintronic devices.